Student Proportional Reasoning on Missing Value Problems Based on Multiplicative Concepts - M Nur, Isman; Diah Prawitha Sari; Saleh, Rusmin (Universitas Pendidikan Ganesha, 2023)
Proportional reasoning involves an understanding of the relationship of the overall multiplicative partitions between ratios and proportions. However, the problem that is often faced by students in proportional reasoning is that students tend to use additive strategies which can cause students to get incorrect answers. This study aims to analyze and describe students' proportional reasoning in solving the missing value problem based on the multiplicative concept. The research design used a qualitative approach with exploratory descriptive type. The research subjects were 3 students of grade VII. Research subjects were selected based on their oral and written communication skills and the considerations of mathematics teachers. Collecting data using the missing value problem solving test and interview guidelines. Data analysis based on the results of student work and the results of interviews directed to determine the research focus in the form of characteristics and indicators of proportional reasoning. The results of the study found three categories of students' proportional reasoning in solving the missing value problem, namely the